Empower employees to step away, with the greater goal of enhancing leadership. Issue 8 (17th April 2018) - Skipworth, Stan
Abstract : News, sports scores, documents, music, television, and movies — all are instantly available. The descriptions of the very devices we choose to access these various information sources and systems highlight their speed: A computer with significantly greater memory and an enhanced processor and faster internet service create the expectation we are capable of handling greater amounts of data, will have a more enjoyable online experience, and will be more effective at work.